Pengaruh Penerapan Terapi Bermain Menggambar dan Mewarnai Untuk Meningkatkan Kreativitas pada Anak Prasekolah di TK Kumara Asih Karang Bedil Mataram - Haryani Haryani; Zurriyatun Thoyibah; Sri Hardiani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction: one of the abilities that must be developed in the education of preschool aged children is children's creativity, especially children's ability to draw and color. Because drawing and coloring are types of activities that children really like to develop children's inventiveness and creativity by expressing all their ideas and imagination through scribbles and scratches and ending it with a period of making pictures that are similar to the object being drawn. Objective: This research aims to determine the effect of applying drawing and coloring play therapy in increasing creativity in children. Design: This study used a pre-experimental design with a one group pre-posttest design on a sample of 16 children aged 4-5 years. Results: The research results showed that before the drawing and coloring play therapy, there were 18.8% in the high creativity category, 25% in the medium creativity category and 56.2% in the low creativity category. Furthermore, after playing therapy with drawing and coloring, there was a change to 93.8% in the high creativity category and 6.2% in the medium creativity category. Conclusion: The results of the analysis using the dependent t test showed p=0.000 (p<0.05), which means there is an influence of the application of drawing and coloring play therapy in increasing creativity in children.